Lack of association between cluster headache and PER3 clock gene polymorphism - Ofte, Hilde K. (J Headache Pain, 2016)
BACKGROUND: Cluster headache (CH) is regarded as a chronobiological disorder. The hypothalamic biological clock may thus be involved in the pathophysiology, but few studies have actually investigated this in CH patients. A variable number tandem repeat (VNTR) polymorphism of the PER3 clock gene has been associated to preferred daily rhythm (chronotype) in several studies. We aimed to study the distribution of PER3 VNTR polymorphisms and chronotypes in a CH population. METHODS: We used blood samples from a biobank of CH patients for genetic tests, and invited all tested patients to complete the Horne-Ostberg Morningness-eveningness Questionnaire (MEQ), the Pittsburgh sleep quality Index (PSQI) and the Shift Work Index. Genotypes were compared to a previously tested population of 432 healthy students. RESULTS: One hundred forty nine patients were genotyped, and we found no difference in PER3 VNTR polymorphisms between patients and controls. Seventy-four patients completed the MEQ (54 men, 20 women, mean age 52.3 years ± 13.4), and chronotypes were as follows: 12 % morning-, 37 % intermediate-, and 51 % evening types. Compared with a previous Danish study of CH patients and controls, there were no difference in chronotype distribution. Sixty percent of patients were defined as bad sleepers (PSQI >5), and 51 % of patients currently employed were shift workers. CONCLUSIONS: No association between CH, PER3 VNTR polymorphism and chronotype was found in this study.